A Short Introduction to Sonoelectrochemistry. (1st January 2018) - Pollet, Bruno G.
Abstract : Sonoelectrochemistry is the effect of ultrasound in electrochemistry (including electroanalysis, corrosion, electrochemistry in environmental applications, organic electrosynthesis, electrodeposition, and electropolymerisation) but also the use of sonoelectrochemistry as a tool to investigate cavitation bubble dynamics and flow velocities as well as the production of nanomaterials (e.g., fuel cell and electrolyser electrocatalysts) and useful gases (e.g., hydrogen).